Retrograde intubation in a case of cancrum oris with sygnathia - Deo, G P; Shrestha, S K; Neupane, S; Ojha, H; Shrestha, I N; Regmi, B S; Subedi, S (Journal of Chitwan Medical College, 2017)
Difficult intubating conditions, anticipated or unanticipated, are part of every anaesthesist’s life. A large number of aids and various techniques have been described for intubating in such situations. The primary job of the anesthesiologist is to secure the airway and provide adequate ventilation to the anesthetised patient. Failure to manage difficult airway has led to many of the total deaths attributable to anesthesia. Proper airway examination and selection of appropriate method for airway intervention is of utmost importance. The retrograde intubation technique is one of the valuable alternative options in places where fiberoptic bronchoscope is not readily available or affordable in cases with anticipated difficult airway. We report a case of cancrum oris with sygnathia (fusion of jaw) leading to inability to open mouth posted for bilateral coronoidectomy with osteotomy of fused bone and lip repair. An awake retrograde nasal intubation with light sedation and local block was performed.